2021
DOI: 10.1007/s11695-021-05415-9
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Net Monetary Benefit of Bariatric Surgery: Systematic Review and Meta-Analysis of Cost-Effectiveness Evidences

Abstract: This systematic review aimed to comprehensively synthesize cost-effectiveness evidences of bariatric surgery by pooling incremental net monetary benefits (INB). Twenty-eight full economic evaluation studies comparing bariatric surgery with usual care were identified from five databases. In high-income countries (HICs), bariatric surgery was cost-effective among mixed obesity group (i.e., obesity with/without diabetes) over a 10-year time horizon (pooled INB = $53,063.69; 95% CI $42,647.96, $63,479.43) and life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 63 publications
1
10
0
1
Order By: Relevance
“…Bariatric surgery is highly effective for weight loss in patients with severe obesity, and it may be associated with long-term cost savings. 7,76 For example, the results of a systematic review and meta-analysis of pooled data from bariatric surgery cost-utility research published through July 2019 in high-income countries (including the United States) found that despite high variability of study results, bariatric surgery can be cost-effective vs usual care (ie, pharmacotherapy and/or lifestyle intervention) over 10 years and over a lifetime horizon. 76 Unfortunately, there is a dearth of similar studies modeling the long-term cost impact of bariatric surgery on the US health care system, specifically.…”
Section: Potential Health Care Costs Savings With Obesity Treatmentsmentioning
confidence: 99%
“…Bariatric surgery is highly effective for weight loss in patients with severe obesity, and it may be associated with long-term cost savings. 7,76 For example, the results of a systematic review and meta-analysis of pooled data from bariatric surgery cost-utility research published through July 2019 in high-income countries (including the United States) found that despite high variability of study results, bariatric surgery can be cost-effective vs usual care (ie, pharmacotherapy and/or lifestyle intervention) over 10 years and over a lifetime horizon. 76 Unfortunately, there is a dearth of similar studies modeling the long-term cost impact of bariatric surgery on the US health care system, specifically.…”
Section: Potential Health Care Costs Savings With Obesity Treatmentsmentioning
confidence: 99%
“…Finally, BS appears to be cost-effective, compared to the usual non-surgical therapy for obesity and the related chronic diseases, in terms of drugs, hospitalization, and work days lost, at least in high-income countries [85].…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Even modest weight loss of 5% to 10% can help patients prevent and control weight-related conditions, such as type 2 diabetes . Multiple cost-effective weight management treatments (WMT) can support 5% or greater weight loss, including nutrition counseling, medically supervised dietary interventions (eg, very low-calorie meal replacement), oral AOM (phentermine/topiramate, bupropion/naltrexone, or orlistat), and bariatric surgery . However, less than 5% of eligible individuals receive these WMT, and little is known about their clinical potential to support weight loss among individual patients and populations.…”
Section: Introductionmentioning
confidence: 99%